Disparities in HPV vaccination rates and HPV prevalence in the United States: a review of the literature - Jacqueline Hirth (Taylor & Francis Group, 2019)
Human papillomavirus (HPV) is a common sexually transmitted infection which is the cause of several cancers, including cervical cancer, and genital warts. Although cervical cancer can be prevented through screening, this cancer persists in the US. More recently, HPV vaccination has the potential to decrease the burden of HPV-related disease among young HPV-unexposed adolescents. Several initiatives aimed to encourage HPV vaccination have been adopted. Unfortunately, uptake of the HPV vaccine remains modest, despite evidence that vaccine-type HPV prevalence is decreasing as a result of HPV vaccination. Further, geographic disparities in vaccination uptake across different US regions and by race/ethnicity may contribute to continuing disparities in HPV-related cancers. More data are needed to evaluate impact of HPV vaccination on HPV prevalence in smaller geographic areas. Further, more information is needed on the impact of individual vaccination programs and policy on population level vaccination and HPV prevalence.